Induction of LabourGuideline of the DGGG, OEGGG and SGGG (S2k, AWMF Registry No. 015-088, December 2020) - Kehl, Sven; Hösli, Irene; Pecks, Ulrich; Reif, Philipp; Schild, Ralf L.; Schmidt, Markus; Schmitz, Dagmar; Schwarz, Christiane; Surbek, Daniel; Abou-Dakn, Michael (Geburtshilfe und Frauenheilkunde, 2021)
Aim The aim of this official guideline published and coordinated by the German Society of Gynaecology and Obstetrics (DGGG) in cooperation with the Austrian Society of Gynaecology and Obstetrics (OEGGG) and the Swiss Society of Gynaecology and Obstetrics (SGGG) is to provide a consensus-based overview of the indications, methods and general management of induction of labour by evaluating the relevant literature. Methods This S2k guideline was developed using a structured consensus process which included representative members from various professions; the guideline was commissioned by the guidelines commission of the DGGG, OEGGG and SGGG. Recommendations The guideline provides recommendations on the indications, management, methods, monitoring and special situations occurring in the context of inducing labour.
CRIS-Team Scopus Importer:2021-08-20
Keywords: guideline; indication; induction; methods; prostaglandin